Riboflavin and ultraviolet light: impact on dengue virus infectivity. Issue 3 (9th June 2016) - Faddy, H. M.; Fryk, J. J.; Watterson, D.; Young, P. R.; Modhiran, N.; Muller, D. A.; Keil, S. D.; Goodrich, R. P.; Marks, D. C.
Abstract : Background: Dengue viruses (DENV 1‐4) are emerging across the world, and these viruses pose a risk to transfusion safety. Pathogen inactivation may be an alternative approach for managing the risk of DENV transfusion transmission. This study aimed to investigate the ability of riboflavin and UV light to inactivate DENV 1‐4 in platelet concentrates. Materials and Methods: DENV 1‐4 were spiked into buffy coat‐derived platelet concentrates in additive solution (SSP+) before being treated with riboflavin and UV light. Infectious virus was quantified pre‐ and posttreatment, and the reduction in viral infectivity was calculated. Results: All four DENV serotypes were modestly reduced after treatment. The greatest amount of reduction in infectivity was observed for DENV‐4 (1·81 log reduction) followed by DENV‐3 (1·71 log reduction), DENV‐2 (1·45 log reduction) and then DENV‐1 (1·28 log reduction). Conclusion: Our study demonstrates that DENV 1‐4 titres are modestly reduced following treatment with riboflavin and UV light. With the increasing number of transfusion‐transmitted cases of DENV around the globe, and the increasing incidence and geographical distribution of DENV, additional approaches for maintaining blood safety may be required in the future.